COUP orphan receptors are negative regulators of retinoic acid response pathways. - Tran, P (1992)
The vitamin hormone retinoic acid (RA) regulates many complex biological programs. The hormonal signals are mediated at the level of transcription by multiple nuclear receptors. These receptors belong to the steroid/thyroid hormone receptor superfamily that also includes a large number of orphan receptors whose biological roles have not yet been determined. Although much has been learned in recent years about RA receptor (RAR) functions, little is known about how specific RA response programs are restricted to certain tissues and cell types during development and in the adult. It has been recently shown that RAR activities are regulated by retinoid X receptors (RXR) through heterodimer formation. In an effort to isolate and further characterize nuclear receptors that modulate RAR and/or RXR activities, we have screened cDNA libraries by using a RXR alpha cDNA probe. Two clones, COUP alpha and COUP beta, identical and closely related to the orphan receptor COUP-TF, were obtained. We show that COUP proteins dramatically inhibit retinoid receptor activities on certain response elements that are activated by RAR/RXR heterodimers or RXR homodimers. COUP alpha and -beta bind strongly to these response elements, including a palindromic thyroid hormone response element and a direct repeat RA response element as well as an RXR-specific response element. In addition, we found that the previously identified COUP-TF binding site in the ovalbumin gene functions in vitro as an RA response element that is repressed in the presence of COUP. Our data suggest that the COUP receptors are a novel class of RAR and RXR regulators that can restrict RA signaling to certain elements. The COUP orphan receptors may thus play an important role in cell- or tissue-specific repression of subsets of RA-sensitive programs during development and in the adult.